Predicting asymptomatic severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection rates of inpatients: A time-series analysis. (24th November 2022) - Rivera, Frida; Ahn, Kwang Woo; Munoz-Price, L. Silvia
Abstract: Asymptomatic SARS-CoV-2 infections are often difficult to identify because widespread surveillance has not been the norm. Using time-series analyses, we examined whether COVID-19 rates at the county level could predict positivity rates among asymptomatic patients in a large health system. Asymptomatic positivity rates at the system level and county-level COVID-19 rates were not associated.